Developing An Educational Board Game with Digital Question Cards : A TGT Model Approach to Enhance Natural and Social Sciences Learning Outcomes - Dwi Arifa; Dewi Nilam Tyas (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to develop and test the feasibility and effectiveness of an educational board game assisted by digital question cards with the Teams Games Tournament (TGT) model. This research and development used Sugiyono's model with stages of potential and problems, data collection, product design, design validation, design revision, product trial, product revision, usage trial, and product revision. Data collection techniques included interviews, questionnaires, tests, and documentation. The subjects of this study were fifth-grade elementary school students. Data analysis techniques included the normality test as a prerequisite test, paired sample t-test or Wilcoxon signed-rank test, and N-Gain test. The board game that has been developed consists of concrete and digital components. The assessment from media and material experts was 94% and 96.6%, so it was categorized as very feasible. The board game was considered effective with an Asymp. Sig (2-tailed) in the usage trial of 0.000 so that Ha is accepted and H0 is rejected. The N-Gain score was 0.7058, with high criteria. The board game media was also considered very practical, with the results of the teacher and student response questionnaires amounting to 98.75% and 94.32%. So, the educational board game media assisted by digital question cards with the TGT model that researchers have developed is very feasible and effective in enhancing Natural and Social Sciences (IPAS) learning outcomes.